Graph the function y = -2|x – 7| + 4 as follows: a. Starting with the expression for the absolute value function y = |x| deduce the sequence of transformations needed to create the specified function. Note: For instance, if we were given the function y = -3(x – 4)2 + 1 we would start with the quadratic function y = x2 and the sequence of transformations would be: - Shift right 4 units, yielding y = (x – 4)2 - Stretch by a factor of 3, yielding y = 3(x – 4)2 - Reflect about the x-axis, yielding y = -3(x – 4)2 - Shift upward 1 unit, yielding y = -3(x – 4)2 + 1 b. Graph each transformation in the sequence on the same set of axes.

Asked By Ariel On 10/09/2017 23:40

Answers

translate right 7 |x - 7| reflect across the x-axis (-) and stretch by a factor of 2 (-2) translate up 4 (+4)
Answered On 10/10/2017 02:50